2006
DOI: 10.1002/ajhb.20488
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of sexual dimorphism in human senescence: Theory, evidence, and causation

Abstract: Age-specific mortality rates of men are higher than those of women, and men have shorter average life spans than women. This has been interpreted as evidence of sexual dimorphism in rates of senescence. However, because mortality can be caused by numerous factors in addition to senescence, higher mortality rates do not necessarily indicate more rapid senescence. In this paper, we (1) emphasize the necessity of decoupling mortality and senescence when considering sexual dimorphism in senescence, (2) present a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Although these results help to build a general framework for understanding the evolution of sexual dimorphism in age-specific life histories, we believe they also have important implications for human aging. Biodemographers studying aging in contemporary human populations have been recently confronted with a ''health-survival paradox'' [6]: men are healthier than women, particularly in late ages, but die younger [6,25,26,39,40]. Recent developments in the evolutionary theory of aging and the results of this study may help resolve the paradox: stronger selection on males may render them less prone to the ravages of old age than females, in spite of males having higher rates of extrinsic mortality.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Although these results help to build a general framework for understanding the evolution of sexual dimorphism in age-specific life histories, we believe they also have important implications for human aging. Biodemographers studying aging in contemporary human populations have been recently confronted with a ''health-survival paradox'' [6]: men are healthier than women, particularly in late ages, but die younger [6,25,26,39,40]. Recent developments in the evolutionary theory of aging and the results of this study may help resolve the paradox: stronger selection on males may render them less prone to the ravages of old age than females, in spite of males having higher rates of extrinsic mortality.…”
Section: Resultsmentioning
confidence: 83%
“…Despite strong interest in sex differences in longevity in the fields of human biodemography and evolutionary biology, our understanding of this phenomenon is very incomplete [5][6][7][24][25][26]. The prediction derived from classic evolutionary theory Males from populations evolving under condition-dependent mortality (orange circles), based on the speed with which they were able to locate virgin females, indeed evolved to do so faster than males from populations evolving under random extrinsic mortality (blue circles) after 20 generation transfers.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the reliance on mortality rates as indicators of senescence, this general pattern has been interpreted as evidence that males senesce more rapidly than females (Williams 1957;Promislow 1991;Perlo and Fretts 2001;Carey 2003). However, Graves et al (2006) have suggested that, at least with regard to humans, direct physiological measures of senescence indicate that males actually senesce more slowly than females. Still, it seems logical that higher mortality would reduce the strength of selection on males and should lead to earlier senescence in males.…”
mentioning
confidence: 96%
“…Given that the functions of mtDNA-encoded gene products have been finetuned in females only, it is possible that mitochondria will be generally less well adapted to cope with higher metabolic demands in males than in females, particularly in tissues that demand high oxygen levels. This may make mitochondrial function in general, and the underlying mtDNA sequence in particular, in males more susceptible to damage than in females and contribute to the well-established longevity gap between the sexes [48][49][50][51][52][53]. Moreover, hypothesized higher production of ROS in males owing to sex-differences in life history [54,55], or in mitochondrial uncoupling [56] may lead to higher ROS-related damage in males compared with females.…”
Section: The Ageing Malementioning
confidence: 99%